Porous crystalline quinolyl organic framework photocatalytic material as well as preparation method and application thereof

By preparing porous crystalline quinolinyl organic frame materials, the stability and photocatalytic performance of covalent organic frames under acidic or alkaline conditions are solved, and efficient photocatalytic hydrogen evolution effect and chemical stability are achieved, especially in loading In the case of Pt, excellent photocatalytic performance is shown.

CN119119401AActive Publication Date: 2024-12-13HAINAN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411045817.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-01
Publication Date
2024-12-13
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

The existing covalent organic framework materials are prone to hydrolysis under acidic or alkaline conditions, and imine bonds hinder charge separation and transfer, affecting their photocatalytic hydrogen evolution properties, and lack of chemical stability.

Method used

Using the preparation method of porous crystalline quinolinyl organic frame material, imine bonds are synthesized under specific conditions by reacting 1,3,6,8-tetrade (4-formaldehyde phenyl)pyrene and para-phenylenediamine. The frame is modified with aromatic alkyne to form a porous crystalline quinolinyl organic frame, and the metal such as Pt is loaded to enhance photocatalytic properties.

Benefits of technology

Chemical stability and high photocatalytic hydrogen evolution efficiency under strong acid or strong alkali conditions were achieved, and good cycle stability and photocatalytic performance were demonstrated, especially when Pt was supported, which showed ultra-high photocatalytic hydrogen evolution efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119401A_ABST
    Figure CN119119401A_ABST
Patent Text Reader

Abstract

The invention provides a porous crystalline quinolyl organic framework photocatalytic material and a preparation method thereof.The preparation method comprises the steps that firstly, reaction monomers 1, 3, 6, 8-tetra (4-formylphenyl) pyrene and p-phenylenediamine are added into a mixed solvent to be evenly mixed, then a catalyst glacial acetic acid is added, a reaction is conducted at the temperature of 100-150 DEG C in the nitrogen atmosphere, an imine bond framework compound is obtained, and the porous crystalline quinolyl organic framework photocatalytic material is obtained; and then uniformly dispersing the imine bond framework compound and aromatic alkyne in a solvent, adding a catalyst trifluoro boron diethyl ether and chloranil, and reacting at 100-150 DEG C in a nitrogen atmosphere to obtain the porous crystalline quinolyl organic framework photocatalytic material. The material has a stable crystal structure, uniform pore size distribution and good chemical stability. Under an illumination condition, the Pt-loaded porous crystalline quinolyl organic framework photocatalytic material shows ultrahigh photocatalytic hydrogen evolution efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of covalent organic framework materials, and in particular to a porous crystalline quinoline-based organic framework photocatalytic material and a preparation method and application thereof. Background Art

[0002] With the increasing concern about the global energy crisis and environmental pollution, the demand for clean and renewable energy is rapidly increasing. Hydrogen energy is considered to be one of the most promising options to replace fossil fuels due to its environmental protection, cost-effectiveness and renewable advantages. Therefore, photocatalytic hydrogen evolution has become a popular research direction. Metal-free covalent organic frameworks (COFs) have the characteristics of high crystallinity, strong π-bridging and structural designability, showing great potential for photocatalytic hydrogen evolution in semiconductor polymer photocatalysts. COFs have diverse framework structures, large specific surface area and porosity, and their parameters such as morphology and hydrophilicity can be precisely controlled, which are crucial for optimizing their photocatalytic performance. In addition, the modular nature of COFs makes it possible to integrate various functional groups and design hierarchical structures, further expanding their potential in photocatalysis.

[0003] Despite remarkable progress in the synthesis of COFs, optimizing their chemical stability and application performance remains a major challenge. For example, imine-linked COFs are susceptible to hydrolysis under acidic conditions and are easily affected by amine exchange, which may weaken their structure and affect durability. In addition, the suboptimal electron delocalization of the imine bond hinders the charge separation and transfer required for efficient photocatalysis. Therefore, solving these challenges can better realize the potential of COFs in photocatalytic hydrogen evolution.

[0004] In order to construct highly stable and fully conjugated COFs, new chemical approaches have been explored through innovative synthetic strategies. One of the approaches involves combining a reversible imine formation reaction with an irreversible post-synthetic modification reaction, which can significantly improve the stability of the resulting COFs. The introduction of oxygen-containing heterocycles such as oxazole, thiazole, and quinoline into the framework through post-synthetic modification has been shown to improve the structural stability of imine COFs. However, despite the improvements in structural stability achieved by these modifications, the application performance of COFs in photocatalytic hydrogen evolution remains to be explored. Therefore, the design and synthesis of new covalent organic framework materials functionalized with quinoline shows attractive application prospects in the field of photocatalytic hydrogen evolution. Summary of the invention

[0005] In view of this, the present invention proposes a porous crystalline quinoline-based organic framework photocatalytic material and a preparation method and application thereof, the purpose of which is to construct a new covalent organic framework material functionalized with quinoline, and further improve the performance of COFs in photocatalytic hydrogen evolution.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The present invention provides a porous crystalline quinoline-based organic framework photocatalytic material, the structural formula of which is:

[0008]

[0009] The present invention also provides a method for preparing the porous crystalline quinoline-based organic framework photocatalytic material, comprising the following steps:

[0010] (1) weighing reaction monomers 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and p-phenylenediamine, adding them into a mixed solvent, mixing them evenly, then adding a catalyst, reacting them at 100 to 150° C. for 24 to 72 hours under a nitrogen atmosphere, and filtering, washing, and drying to obtain an imine bond framework compound after the reaction is completed;

[0011] (2) The imine bond framework compound and the aromatic alkyne are uniformly dispersed in a solvent, a catalyst is added, and the mixture is reacted at 100 to 150° C. for 24 to 72 hours under a N2 atmosphere; after the reaction, the mixture is filtered, washed, and dried to obtain a porous crystalline quinoline-based organic framework photocatalytic material, which is recorded as Qu-CN-COF.

[0012] Preferably, the stoichiometric ratio of the reaction monomers 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and p-phenylenediamine is 1:2; the mixed solvent is o-dichlorobenzene and n-butanol, and the volume ratio of o-dichlorobenzene and n-butanol is 1:1 to 4:1; the mass volume ratio of the reaction monomer to the mixed solvent is 1 mg:30 μL.

[0013] Preferably, the catalyst in (1) is 6M glacial acetic acid solution; and the catalyst in (2) is boron trifluoride etherate and tetrachlorobenzoquinone.

[0014] Preferably, the molar ratio of the imine bond framework material to the aromatic alkyne is 1:1-3; the molar ratio of boron trifluoride etherate, tetrachlorobenzoquinone and aromatic alkyne is 1:1:1-1:1:3.

[0015] Preferably, the aromatic alkyne in (2) is 4-ethynylbenzonitrile, and the solvent is any one of toluene, acetone and carbon tetrachloride.

[0016] Preferably, the solvent used for the washing is at least one of tetrahydrofuran and ethanol.

[0017] A porous crystalline quinoline-based organic framework photocatalytic material is prepared by any preparation method described in the present invention.

[0018] The present invention also provides application of the porous crystalline quinoline-based organic framework photocatalytic material in photocatalytic hydrogen production.

[0019] Preferably, the porous crystalline quinoline-based covalent organic framework is loaded with metals and used as a catalyst for photocatalytic hydrogen production, and the metal elements include one or more of Cu, Pt, Ir, Pd, Ni, Co and Ru.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material and a preparation method thereof. The material has a novel structure, a simple preparation process, is cheap and readily available, and the quinoline-based covalent organic framework material of the present invention has a stable crystal structure and a uniform pore size distribution. Compared with an imine bond framework, the quinoline-based covalent organic framework material of the present invention also has good chemical stability, and the crystalline structure is still relatively stable in a strong acid or strong base solution. Under illumination conditions, the porous crystalline quinoline-based organic framework (Qu-CN-COF) material loaded with Pt exhibits an ultra-high photocatalytic hydrogen evolution efficiency, and exhibits broad application prospects in the field of photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the synthesis of porous crystalline quinoline-based organic framework photocatalytic materials

[0023] Figure 2 This is the N2 adsorption-desorption curve of the porous crystalline imine bond covalent organic framework (TF-PD-COF) photocatalytic material obtained in Example 1 at 77K.

[0024] Figure 3 This is the pore size distribution curve of the porous crystalline imine bond covalent organic framework (TF-PD-COF) photocatalytic material of Example 1 calculated by the NLDFT method.

[0025] Figure 4 This is the infrared spectrum of the porous crystalline covalent imine bond organic framework (TF-PD-COF) photocatalytic material obtained in Example 1.

[0026] Figure 5 This is the N2 adsorption-desorption curve of the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material obtained in Example 1 at 77K.

[0027] Figure 6 This is the pore size distribution curve of the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material of Example 1 calculated by the NLDFT method.

[0028] Figure 7 This is the infrared spectrum of the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material obtained in Example 1.

[0029] Figure 8 This is a hydrogen production cycle performance diagram of the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material obtained in Example 1.

[0030] Fig. 9 The X-ray diffraction spectra of the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material obtained in Example 1 before and after acid-base treatment. DETAILED DESCRIPTION

[0031] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0032] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0033] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0034] The synthesis route of the porous crystalline quinoline-based organic framework photocatalytic material of the embodiment of the present invention is as follows Figure 1 shown.

[0035] Example 1

[0036] Synthesis of TF-PD-COF materials

[0037] 1,3,6,8-Tetra(4-formylphenyl)pyrene (24.7 mg, 0.04 mmol), p-phenylenediamine (8.7 mg, 0.08 mmol) and a mixture of o-dichlorobenzene and n-butanol (0.5 / 0.5 mL, v / v) were sequentially charged into a glass ampoule. The mixture was ultrasonically mixed for 10 minutes to make it uniform, and glacial acetic acid (6M, 0.1mL) was added to the mixture as a catalyst. After three cycles of liquid nitrogen freezing-vacuuming-thawing, the glass ampoule was flame-sealed under vacuum conditions and allowed to stand at 120°C for 72 hours. After the reaction, the product was collected and washed three times with tetrahydrofuran and ethanol respectively, then extracted with tetrahydrofuran for 24 hours, and finally heated at 120°C for 12 hours under vacuum conditions to obtain a yellow powder, which is a porous crystalline imine bond organic framework (TF-PD-COF) material with a yield of 75%. The nitrogen adsorption-desorption curve is shown in FIG. Figure 2 As shown, the BET specific surface area is 2506m 2 ·g -1 The type IV isotherm not only shows the mesoporous nature of the framework material, but also the pore size distribution curve of TF-PD-COF calculated by the NLDFT method is shown in Figure 3As shown in the infrared spectrum, the average pore size is 1.68nm. Figure 4 The information analysis results obtained: at 1624cm -1 The characteristic absorption peak of imine bond (C=N) appears at , indicating the synthesis of porous crystalline imine bond organic framework (TF-PD-COF).

[0038] Synthesis of Qu-CN-COF Materials

[0039] TF-PD-COF (158 mg, 0.5 mmol), 4-ethynylbenzonitrile (64 mg, 0.5 mmol), boron trifluoride etherate (BF3·OEt2) (27 μL, 0.215 mmol), tetrachlorobenzoquinone (Chloranil) (53 mg, 0.215 mmol) and 20 mL of toluene were added to a 25 mL hard glass tube, heated in an oil bath at 110 ° C under N2 atmosphere for 72 h, washed with tetrahydrofuran after cooling, quenched with saturated NaHCO3, extracted with tetrahydrofuran for 12 h and dried under vacuum heating at 120 ° C for 24 h to obtain a porous crystalline quinoline organic framework (Qu-CN-COF) photocatalytic material.

[0040] The obtained porous crystalline quinoline organic framework (Qu-CN-COF) photocatalytic material was characterized, and the nitrogen adsorption and desorption curves are shown in the figure. Figure 5 As shown, the BET specific surface area is 1207m 2 ·g -1 The type IV isotherm of Qu-CN-COF not only indicates the mesoporous nature, but also shows that chemical modification does not significantly change the framework structure of COF. The pore size distribution curve of Qu-CN-COF calculated by NLDFT method is shown in Figure 6 As shown, the average pore size is 1.33 nm.

[0041] Infrared spectrum Figure 7 As shown in the figure, the obtained information analysis results: the stretching vibration peak of the prepared COFs was evaluated by Fourier transform infrared (FT-IR). -1 A significant peak appears at 1602 cm, which belongs to C=N vibration, indicating the presence of residual imine bond COFs. At the same time, the stretching frequency of the quinoline functional group corresponding to 1602 cm -1 The characteristic peak at 2228cm -1 The C≡N characteristic peak of Qu-CN-COF appears at .

[0042] Example 2

[0043] Synthesis of TF-PD-COF materials

[0044] 1,3,6,8-Tetrakis(4-formaldehydephenyl)pyrene (24.7 mg), p-phenylenediamine (8.7 mg) and a mixture of o-dichlorobenzene and n-butanol (0.8 / 0.2 mL, v / v) were sequentially placed in a glass ampoule. The mixture was ultrasonicated for 10 minutes to mix evenly. Glacial acetic acid (6M, 0.1 mL) was added to the mixture as a catalyst. After three cycles of liquid nitrogen freezing-vacuuming-thawing, the glass ampoule was flame-sealed under vacuum conditions and allowed to react at 150°C for 24 hours. After the reaction was completed, the product was collected and washed three times with tetrahydrofuran and ethanol respectively, and then extracted with tetrahydrofuran for 24 hours. Finally, it was heated at 120°C under vacuum conditions and dried for 12 hours to obtain a yellow powder, which was a porous crystalline imine bond organic framework (TF-PD-COF) material.

[0045] Synthesis of Qu-CN-COF Materials

[0046] TF-PD-COF (158 mg, 0.5 mmol), 4-ethynylbenzonitrile (64 mg, 0.5 mmol), boron trifluoride etherate (BF3·OEt2) (63 μL, 0.5 mmol), tetrachlorobenzoquinone (Chloranil) (123 mg, 0.5 mmol) and 20 mL of acetone were added to a 25 mL hard glass tube. The mixture was heated in an oil bath at 150 ° C for 24 h under N2 atmosphere, washed with tetrahydrofuran after cooling, quenched with saturated NaHCO3, extracted with tetrahydrofuran for 12 h and dried under vacuum at 120 ° C for 24 h to obtain a porous crystalline quinoline organic framework (Qu-CN-COF) photocatalytic material.

[0047] Example 3

[0048] Synthesis of TF-PD-COF materials

[0049] 1,3,6,8-Tetrakis(4-formaldehydephenyl)pyrene (24.7 mg), p-phenylenediamine (8.7 mg) and a mixture of o-dichlorobenzene and n-butanol (0.5 / 0.5 mL, v / v) were sequentially placed in a glass ampoule. The mixture was ultrasonicated for 10 minutes to mix evenly. Glacial acetic acid (6M, 0.1 mL) was added to the mixture as a catalyst. After three cycles of liquid nitrogen freezing-vacuuming-thawing, the glass ampoule was flame-sealed under vacuum conditions and allowed to react at 100 °C for 72 h. After the reaction was completed, the product was collected and washed three times with tetrahydrofuran and ethanol, respectively, and then extracted with tetrahydrofuran for 24 h. Finally, it was heated at 120 °C under vacuum conditions and dried for 12 h to obtain a yellow powder, which was a porous crystalline imine bond organic framework (TF-PD-COF) material.

[0050] Synthesis of Qu-CN-COF Materials

[0051] TF-PD-COF (158 mg, 0.5 mmol), 4-ethynylbenzonitrile (191 mg, 1.5 mmol), boron trifluoride etherate (BF3·OEt2) (63 μL, 0.5 mmol), tetrachlorobenzoquinone (Chloranil) (123 mg, 0.5 mmol) and 20 mL of carbon tetrachloride were added to a 25 mL hard glass tube. The mixture was heated in an oil bath at 100 ° C for 72 h under N2 atmosphere, washed with tetrahydrofuran after cooling, quenched with saturated NaHCO3, extracted with tetrahydrofuran for 12 h and dried under vacuum at 120 ° C for 24 h to obtain a porous crystalline quinoline organic framework (Qu-CN-COF) photocatalytic material.

[0052] Comparative Example 1

[0053] This comparative example is the TF-PD-COF material obtained in the first step of Example 1.

[0054] Synthesis of TF-PD-COF materials

[0055] 1,3,6,8-Tetra(4-formylphenyl)pyrene (24.7 mg), p-phenylenediamine (8.7 mg) and a mixture of o-dichlorobenzene and n-butanol (0.5 / 0.5 mL, v / v) were sequentially placed in a glass ampoule. The mixture was ultrasonically mixed for 10 min to make it uniform. Glacial acetic acid (6M, 0.1 mL) was added to the mixture as a catalyst. After three cycles of liquid nitrogen freezing-vacuuming-thawing, the glass ampoule was flame-sealed under vacuum conditions and allowed to react at 120°C for 72 h. After the reaction was completed, the product was collected and washed three times with tetrahydrofuran and ethanol, respectively, and then extracted with tetrahydrofuran for 24 h. Finally, it was heated at 120°C under vacuum conditions and dried for 12 h to obtain a yellow powder, which was the product TF-PD-COF.

[0056] Comparative Example 2

[0057] The difference from Example 1 is that 4-ethynylbenzonitrile is replaced by phenylacetylene in the synthesis step of the Qu-CN-COF material, and the other operations are consistent with Example 1.

[0058] Experimental Example 1 Photocatalytic hydrogen evolution performance test of Qu-CN-COF material

[0059] The photocatalytic H2 production experiment was carried out in a top-irradiated photoreactor (Pyrex glass) connected to a closed gas circulation system. The hydrogen production efficiency is calculated based on the peak area. Experimental method: The organic framework photocatalytic material powder (1 mg) obtained in Examples 1-3 and Comparative Examples 1-2 was dispersed in 100 mL of a mixed aqueous solution containing 0.1 M ascorbic acid, and a calculated amount of H2PtCl6 was dissolved in the suspension, and 5.0 wt.% Pt was deposited on the catalyst surface by photodeposition. The temperature was fixed at 283 K by circulating water, and the photocatalytic H2 evolution was evaluated using a 300 W xenon lamp (wavelength between 350 nm and 780 nm). The generated hydrogen was measured by a gas chromatograph (GC) equipped with a thermal conductivity detector (TCD) using argon as a carrier gas. The results of photocatalytic hydrogen production within 4 h are shown in Table 1.

[0060] Table 1 Photocatalytic hydrogen production

[0061]

[0062] It can be seen from the results in Table 1 that, under the same Pt ​​loading, the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material obtained in Examples 1-3 of the present invention, when used as a carrier, exhibits excellent performance in the photocatalytic hydrogen production performance test, and the hydrogen production within 4 hours can reach 1049.31 mmol·g -1 When the materials obtained in Comparative Examples 1 and 2 are used as carriers, the photocatalytic hydrogen production performance is significantly reduced.

[0063] The hydrogen production cycle performance results of the porous crystalline quinoline organic framework (Qu-CN-COF) photocatalytic material obtained in Example 1 are as follows: Figure 8 As shown in the figure, the catalytic activity for hydrogen evolution is still high after 24 hours of reaction, and it has good cycle stability.

[0064] Test Example 2 Chemical Stability Test of Qu-CN-COF

[0065] The porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material prepared in Example 1 was dispersed in 12 mol / L hydrochloric acid and 14 mol / L sodium hydroxide aqueous solution at room temperature, respectively, for 72 h, and then filtered. The filter cake was washed with water and tetrahydrofuran, respectively, and characterized by a powder X-ray diffractometer after drying.

[0066] The results are as follows Fig. 9 As shown, the X-ray diffraction spectrum of the porous crystalline quinoline-based organic framework photocatalytic material prepared in Example 1 remains almost unchanged before and after immersion in strong acid and strong base, indicating that the porous crystalline quinoline-based organic framework (Qu-CN-COF) photocatalytic material maintains the original topological structure and pore size and has good chemical stability.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A porous crystalline quinoline-based organic framework photocatalytic material, characterized in that: Its structural formula is:

2. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 1, characterized in that: The following steps are involved: (1) weighing reaction monomers 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and p-phenylenediamine, adding them into a mixed solvent, mixing them evenly, then adding a catalyst, reacting them at 100 to 150° C. for 24 to 72 hours under a nitrogen atmosphere, and filtering, washing, and drying to obtain an imine bond framework compound after the reaction is completed; (2) The imine bond framework compound and the aromatic alkyne are uniformly dispersed in a solvent, a catalyst is added, and the mixture is reacted at 100-150° C. for 24-72 hours under a N2 atmosphere. After the reaction is completed, the mixture is filtered, washed, and dried to obtain a porous crystalline quinoline-based organic framework photocatalytic material, which is recorded as Qu-CN-COF.

3. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 2, characterized in that: The chemical stoichiometric ratio of the reaction monomers 1,3,6,8-tetrakis(4-formaldehydephenyl)pyrene and p-phenylenediamine is 1:2; the mixed solvent is o-dichlorobenzene and n-butanol, the volume ratio of o-dichlorobenzene and n-butanol is 1:1-4:1, and the mass volume ratio of the reaction monomer to the mixed solvent is 1 mg:30 μL.

4. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 2, characterized in that: The catalyst in step (1) is 6M glacial acetic acid solution; the catalyst in step (2) is boron trifluoride etherate and tetrachlorobenzoquinone.

5. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 2, characterized in that: The molar ratio of the imine bond framework material to the aromatic alkyne is 1:1-3; the molar ratio of boron trifluoride etherate, tetrachlorobenzoquinone and the aromatic alkyne is 1:1:1-1:1:

3.

6. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 2, characterized in that: In the step (2), the aromatic alkyne is 4-ethynylbenzonitrile, and the solvent is any one of toluene, acetone, and carbon tetrachloride.

7. The method for preparing a porous crystalline quinoline-based organic framework photocatalytic material according to claim 2, characterized in that: The solvent used for the washing is at least one of tetrahydrofuran and ethanol.

8. A porous crystalline quinoline-based organic framework photocatalytic material, prepared by the preparation method according to any one of claims 2 to 7.

9. Use of the porous crystalline quinoline-based organic framework photocatalytic material according to claim 1 in photocatalytic hydrogen production.

10. The use according to claim 9, characterized in that: The porous crystalline quinoline-based covalent organic framework is loaded with metals and used as a catalyst for photocatalytic hydrogen production, wherein the metal elements include one or more of Cu, Pt, Ir, Pd, Ni, Co and Ru.

Citation Information

Patent Citations

  • Covalent organic framework material serving as hydrogen evolution catalyst as well as preparation method and application thereof

    CN114016068A

  • Quinoline ring connection-based covalent organic framework material and preparation method thereof

    CN114292412A

  • Preparation method and product of non-substituted quinoline bridged covalent organic framework

    CN115010883A

  • Porous crystalline quinolyl organic framework rich in (NN)-ligand element, and preparation method and application thereof

    CN115785365A

  • Pyrenyl covalent organic framework polymer photocatalyst, preparation method thereof and application of pyrenyl covalent organic framework polymer photocatalyst in hydrogen production by photocatalytic decomposition of water

    CN116217849A